Scientometric analysis of pavement maintenance: a twenty-year review - Ji, Ankang; Xue, Xiaolong; Luo, Xiaowei; Wang, Yuna; Wu, Hengqin (Journal of Civil Engineering and Management, 2023)
Pavement maintenance is widely thought to be critical for promoting sustainability, playing a pivotal role in sustainable and resilient transportation infrastructure for growth in economic development and improvements in social inclusion. It has attracted increasing attention from both academia and industry over the past 20 years. Although several literature reviews have been conducted, there is still a lack of systematic quantitative and visual investigation of the structure and evolution of knowledge in this field. To address this lack, reported here is a comprehensive and objective scientometric analysis to visualize the status quo of research areas regarding pavement maintenance. Focusing on 614 journal articles collected from the Web of Science for 2001–2020, key researchers within the field are identified, as are the key research institutions, key countries, and their interconnections, as well as keywords, evolution trends, key publications, and citation patterns, along with the extent to which these interact with each other in research networks. Based on the in-depth analysis, a knowledge roadmap is provided to inscribe how pavement maintenance-related research evolves over time, greatly contributing to the understanding of the underlying structure of pavement maintenance, and to highlight the identified current research challenges and future research trends, thus potentially benefiting the academic community and practice field on multiple themes of pavement maintenance. The results of this research are instructive, providing a broad overview and holistic thinking for researchers and practitioners with respect to pavement maintenance research, as well as facilitating further research and applications for both academia and industry in improving pavement maintenance for sustainability.